The paradox of dicer in cancer - Swahari, Vijay (Mol Cell Oncol, 2016)
Dicer has been well studied in cancer; however, deciphering its exact function in tumorigenesis continues to be a challenge. While partial suppression or truncation of Dicer promotes tumorigenesis, its complete deletion inhibits tumor growth. Here, we discuss this Dicer cancer conundrum in the context of its recently discovered role in the DNA damage response.